Preparing Future Biology Teachers for Sustainability: The Role of Environmental Literacy in Achieving Sustainable Development Goals (SDGs) - Zevira Fransisca Aurora; Ulya Ruwaida; Rina Oktaviana; Opik Prasetyo; Hery Fajeriadi; Nurul Aulia; Nazwa Nabila (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2026)
Environmental challenges such as ecosystem degradation, biodiversity loss, and pollution have become major threats to sustainability worldwide. Despite the growing importance of environmental literacy for achieving sustainability goals, limited studies have examined the environmental literacy of prospective biology teachers, particularly within wetland ecosystem contexts. This study aimed to assess the environmental literacy of biology education students and explore its contribution to achieving Sustainable Development Goals (SDGs) through sustainability oriented education. This research employed a convergent mixed methods approach involving 58 biology education students selected through purposive sampling. Data were collected using questionnaires and interviews and analyzed through descriptive statistics and thematic analysis. The findings revealed high levels of environmental knowledge, awareness, and conservation attitudes among students, whereas pro-environmental behavior remained at a moderate level, indicating a gap between environmental understanding and actual practice. Students also demonstrated strong awareness of the importance of conserving wetland ecosystems and recognized the role of education in promoting sustainability. These findings highlight the importance of strengthening environmental literacy among prospective biology teachers to support SDG 4 (Quality Education), SDG 13 (Climate Action), and SDG 15 (Life on Land) through sustainability oriented education.